2008
DOI: 10.1021/ac7024915
|View full text |Cite
|
Sign up to set email alerts
|

Direct Introduction of Biological Samples into a LTQ-Orbitrap Hybrid Mass Spectrometer as a Tool for Fast Metabolome Analysis

Abstract: We report the direct introduction of biological samples into a high-resolution mass spectrometer, the LTQ-Orbitrap, as a fast tool for metabolomic studies. A proof of concept study was performed on yeast cell extracts that were introduced into the mass spectrometer by using flow injection analysis, with an acquisition time of 3 min. Typical mass spectra contained a few thousand m/z signals, 400 of which were found to be analytically relevant (i.e., their intensity was 3-fold higher than that of the background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 53 publications
1
85
0
Order By: Relevance
“…High-resolution ESI MS has previously been used to study covalent and non-covalent ligand-biomolecule interactions [37,38] and to screen complex mixtures of metabolites [39][40][41], often without the need for chromatographic separation of the adducts prior to analysis. Hence, this method allows the simultaneous screening of complicated mixtures of compounds with the direct (Ub), cytochrome c (cyt c) and superoxide dismutase (SOD) (1:1:1) in tetramethylammonium acetate (TMeAmAc) buffer pH 7.4 and the same protein mixture after 24-h incubation at 37°C with cisplatin, transplatin and RAPTA-C, respectively (5:1 metal-to-protein ratio).…”
Section: Resultsmentioning
confidence: 99%
“…High-resolution ESI MS has previously been used to study covalent and non-covalent ligand-biomolecule interactions [37,38] and to screen complex mixtures of metabolites [39][40][41], often without the need for chromatographic separation of the adducts prior to analysis. Hence, this method allows the simultaneous screening of complicated mixtures of compounds with the direct (Ub), cytochrome c (cyt c) and superoxide dismutase (SOD) (1:1:1) in tetramethylammonium acetate (TMeAmAc) buffer pH 7.4 and the same protein mixture after 24-h incubation at 37°C with cisplatin, transplatin and RAPTA-C, respectively (5:1 metal-to-protein ratio).…”
Section: Resultsmentioning
confidence: 99%
“…It is a fast and reliable tool that has been successfully applied earlier to investigate the metabolic response of S. cerevisiae to cadmium exposure (28). Typical yeast mass spectra contain a few hundred analytically relevant m/z signals.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure has been adapted from Madalinski et al (28). Briefly, the analyses were performed by flow injection analysis by using an Accela pump and an Accela autosampler from Thermo Fisher Scientific (San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
“…212.07, was present in all the samples and blanks and this was assigned to the plasticiser n-butyl benzensulfonamide, an ion that has been used previously as a lockmass in the negative ion mode [42] and was used in this study with the TD-SESI-MS data enabling the target VFAs Figure 2 to be identified with a mass accuracy of 3.5 ppm or less [43].…”
Section: Skin Sample Analysismentioning
confidence: 99%